Functionally confirmed compound heterozygous ADAM17 missense loss-of-function variants cause neonatal inflammatory skin and bowel disease 1 - Issei Imoto (Nature Portfolio, 2021)
Abstract A disintegrin and metalloprotease 17 (ADAM17) is the major sheddase that processes more than 80 substrates, including tumour necrosis factor-α (TNFα). The homozygous genetic deficiency of ADAM17 causing a complete loss of ADAM17 expression was reported to be linked to neonatal inflammatory skin and bowel disease 1 (NISBD1). Here we report for the first time, a family with NISBD1 caused by functionally confirmed compound heterozygous missense variants of ADAM17, namely c.1699T>C (p.Cys567Arg) and c.1799G>A (p.Cys600Tyr). Both variants were detected in two siblings with clinical features of NISBD1, such as erythroderma with exudate in whole body, recurrent skin infection and sepsis and prolonged diarrhoea. In a cell-based assay using Adam10/17 double-knockout mouse embryonic fibroblasts (Adam10/17 −/− mEFs) exogenously expressing each of these mutants, phorbol 12-myristate 13-acetate-stimulated shedding was strongly reduced compared with wild-type ADAM17. Thus, in vitro functional assays demonstrated that both missense variants cause the loss-of-function of ADAM17, resulting in the development of NISBD1. Our study further expands the spectrum of genetic pathology underlying ADAM17 in NISBD1 and establishes functional assay systems for its missense variants.